Glitter up the dark : how pop music broke the binary - Geffen, Sasha (American music series (Austin, Tex.), 2020)
"Is our love of pop music innately queer? That's the question Sasha Geffen answers--with a "yes," of course--in this book. Beginning with the Beatles and moving to the present, Geffen identifies artists of all stripes who performed "outside the limitations of their assigned genders." This includes not only trans artists like Wendy Carlos, or openly gender-bending artists like David Bowie and Prince, but ostensibly cis and hetero artists whose work and performance complicate the binary. This musical androgyny, they argue, is the result of different factors at different points in the timeline, but the flexibility of the human voice in pop music emerges as the most consistent form of expression. Geffen continues right up to the present, covering the origins of House and disco in gay clubs and the utopia of the dance floor, the genderless technology of hip-hop and artists like Missy Elliott who embody masculine virtues"--